2021
DOI: 10.1210/endocr/bqab080
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulation of the Molecular Phenotype and Active Translatome of AVPV Kisspeptin Neurons

Abstract: In females, ovarian estradiol (E2) exerts both negative and positive feedback regulation on the neural circuits governing reproductive hormone secretion, but the cellular and molecular mechanisms underlying this remain poorly understood. In rodents, ERα-expressing kisspeptin neurons in the hypothalamic anteroventral periventricular region (AVPV) are prime candidates to mediate E2 positive feedback induction of preovulatory GnRH and LH surges. E2 stimulates AVPV Kiss1 expression, but the full extent of estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 86 publications
4
41
0
Order By: Relevance
“…While the precise circuit for such phenomenon is yet to be disclosed, the existence of projections of ARC Kiss1 neurons to the rostral preoptic hypothalamic area provides the anatomical substrate for a putative KNDy-born kisspeptin output to the AVPV (Yeo and Herbison 2011) (Stephens and Kauffman 2021). This feature further validates our approach of Tac2driven Cre expression for conditional ablation of Kiss1 in ARC KNDy, but not in AVPV Kiss1 neurons.…”
Section: Kndy-born Kisspeptins and Reproductionsupporting
confidence: 62%
See 1 more Smart Citation
“…While the precise circuit for such phenomenon is yet to be disclosed, the existence of projections of ARC Kiss1 neurons to the rostral preoptic hypothalamic area provides the anatomical substrate for a putative KNDy-born kisspeptin output to the AVPV (Yeo and Herbison 2011) (Stephens and Kauffman 2021). This feature further validates our approach of Tac2driven Cre expression for conditional ablation of Kiss1 in ARC KNDy, but not in AVPV Kiss1 neurons.…”
Section: Kndy-born Kisspeptins and Reproductionsupporting
confidence: 62%
“…The possibility that the defective LH surge seen in our TaKKO female mice may stem from the congenital ablation of at least part of kisspeptin production in the AVPV can be ruled out, since TaKKO females under physiological estradiol replacement displayed fully preserved Kiss1 levels in this rostral hypothalamic area. Furthermore, recent RNA-seq analyses for identification of actively translated mRNA transcripts in AVPV Kiss1 neurons failed to detect Tac2 expression in this neuronal population, despite the observed expression of other KNDy genes, such as Kiss1 and Pdyn (Stephens and Kauffman 2021). This feature further validates our approach of Tac2 - driven Cre expression for conditional ablation of Kiss1 in ARC KNDy, but not in AVPV Kiss1 neurons.…”
Section: Discussionmentioning
confidence: 86%
“…This was supported by a similar report in mice that high-frequency photostimulation of RP3V KISS neurons evokes increased electrical activity in GnRH neurons in several in vitro slice orientations (Qiu et al, 2016). Importantly, although RP3V KISS neurons coexpress many additional releasable signaling factors along with kisspeptin itself (Stephens and Kauffman, 2021), similar in vivo Circadian changes in RP3V KISS neuron activation, measured by cfos mRNA induction, and serum LH levels in OVX + E 2 female mice housed in constant darkness (DD). The onset and peak of RP3V KISS neuron activation mirrors the rise and peak of LH surges, which occur right before the onset of subjective night (defined as the daily onset of locomotor activity, a robust circadian behavioral measure).…”
Section: Estrogen Regulation Of Kisspeptin Neuronsmentioning
confidence: 99%
“…In fact, Ef1a1 is often used as a 'housekeeping' or reference gene as a result of its stable expression. However, two studies showed that Ef1a1 expression can be increased by estradiol in liver tissues of female tadpoles [92] and in neurons in the hypothalamic anteroventral periventricular region of mice [93]. This suggests that higher levels of Igfbp5 protein secreted by pFBs from transgenic female mice in our study may be due to the effect of estrogen, resulting in more pronounced differential expression of downstream target genes.…”
Section: Sex Differences In the Response Of Fibroblastsmentioning
confidence: 59%